2017
DOI: 10.1111/echo.13675
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between myocardial deformation on three‐dimensional speckle tracking echocardiography and cardiopulmonary exercise testing

Abstract: Left ventricular early diastolic function is a modest independent predictor of aerobic exercise capacity. The 25%Untwist value is a good indicator of cardiac diastolic function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Patients with HF usually present with exercise intolerance and the gold standard for assessing clinical cardiopulmonary function is cardiopulmonary exercise testing (CPET) [ 66 ]. Combined with 3D-STE and CPET data from 156 subjects with different levels of cardiac function, Li et al found that the amount of 25% duration untwisting (25% untwist) was positively correlated with peak oxygen uptake (r = 0.41, p < 0.001) and negatively correlated with the CO 2 equivalent slope (r = −0.49, p < 0.001).…”
Section: Three-dimensional Speckle-tracking Echocardiography In Hf Pa...mentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with HF usually present with exercise intolerance and the gold standard for assessing clinical cardiopulmonary function is cardiopulmonary exercise testing (CPET) [ 66 ]. Combined with 3D-STE and CPET data from 156 subjects with different levels of cardiac function, Li et al found that the amount of 25% duration untwisting (25% untwist) was positively correlated with peak oxygen uptake (r = 0.41, p < 0.001) and negatively correlated with the CO 2 equivalent slope (r = −0.49, p < 0.001).…”
Section: Three-dimensional Speckle-tracking Echocardiography In Hf Pa...mentioning
confidence: 99%
“…A total of 25% untwist value was a good indicator of LV early diastolic dysfunction, which is an independent predictor for examining aerobic exercise capacity. Cardiac function of HF patients with dyskinesia can be evaluated as an aid by revealing the relationship between cardiac diastolic function at rest and CPET [ 66 ].…”
Section: Three-dimensional Speckle-tracking Echocardiography In Hf Pa...mentioning
confidence: 99%
“…Other studies have compared STE on patients with HFpEF at rest and during exercise to evaluate prognostic parameters associated with increased risk of hospitalizations. In addition, exercise stress STE may provide an improved assessment of patients with HFpEF and direct treatment options to reduce symptom burden [7779].…”
Section: Role Of Left Atrial Strain In Evaluating Hfpef With Speckle mentioning
confidence: 99%
“…Assessment of left ventricular function by three‐dimensional speckle tracking can be comparable to cardiac nuclear magnetic resonance . It was found that 25% untwist was related to oxygen uptake, which can be used as an independent predictor of aerobic exercise ability and a good indicator of cardiac diastolic function in patients with HF . 3D‐STE can also detect early left ventricular dysfunction caused by hypertrophic cardiomyopathy, essential hypertension, type 2 diabetes mellitus, and chemotherapy drugs .…”
Section: D‐ste In Assessing Myocardial Motionmentioning
confidence: 99%
“…35 It was found that 25% untwist was related to oxygen uptake, which can be used as an F I G U R E 4 Radial strain curves of left ventricular apical segments, obtained by three-dimensional speckle-tracking echocardiography (3D-STE) on short axis view in a patient with cardio-renal syndrome independent predictor of aerobic exercise ability and a good indicator of cardiac diastolic function in patients with HF. 36 3D-STE can also detect early left ventricular dysfunction caused by hypertrophic cardiomyopathy, 37 essential hypertension, 38 type 2 diabetes mellitus, 39 and chemotherapy drugs. 40 In addition to evaluating LV myocardial motion, 3D-STE can also evaluate the left atrium, 41 right atrium, 42…”
Section: Assessing Myocardial Motor Functionmentioning
confidence: 99%